Gene Expression during the Cell Cycle: Obfuscation of Original Cell-Cycle Gene Expression Data by Normalization - Cooper, Stephen (Journal of Cells, 2015)
Normalization of raw data on gene expression during the cell cycle obscures the original experimental data and makes it appear as if all genes have the same numerical level of cyclical expression. Results that would not support gene expression because of minimal variations thus appear, after normalization, to be stronger than they actually are. Consideration of the effect of normalization raises critical questions about many experiments on the cell cycle dependent variation of gene expression—that is, proposed cyclical changes in mRNA content—during the cell cycle.